Special Issue: The Science and Technology of 3D Printing - Tuhin Mukherjee (MDPI AG, 2021)
Additive manufacturing, commonly known as three-dimensional printing (3D printing), is becoming an increasingly popular method for making components that are difficult to fabricate using traditional manufacturing processes [...]